DNA bending potentials for loop-mediated nucleosome repositioning - Biswas, Mithun; Langowski, Jörg; Smith, Jeremy C. (epl, 2012)
Nucleosome repositioning is a fundamental process in gene function. DNA elasticity is a key element of loop-mediated nucleosome repositioning. Two analytical models for DNA elasticity have been proposed: the linear sub-elastic chain (SEC), which allows DNA kinking, and the worm-like chain (WLC), with a harmonic bending potential. In vitro studies have shown that nucleosomes reposition in a discontiguous manner on a segment of DNA and this has also been found in ground-state calculations with the WLC analytical model. Here we study using Monte Carlo simulation the dynamics of DNA loop-mediated nucleosome repositioning at physiological temperatures using the SEC and WLC potentials. At thermal energies both models predict nearest-neighbor repositioning of nucleosomes on DNA, in contrast to the repositioning in jumps observed in experiments. This suggests a crucial role of DNA sequence in nucleosome repositioning.
Gesehen am 17.08.2018